Inocybe plesiocista (Inocybaceae, Agaricales), a new cistophilous species from Mediterranean Europe - Polemis, Elias; Bandini, Ditte; Rodríguez-Campo, Francisco J.; Kottis, Linos; Fryssouli, Vassiliki; Raventós, Fernando Esteve; Zervakis, Georgios I. (Phytotaxa, 2026)
A new species, i.e. Inocybe plesiocista, is described on the basis of unique morphological features, phylogeny, and habitat characteristics. The type specimen was collected under Quercus ilex subsp. ballota (= Q. rotundifolia) and Cistus ladanifer in Spain (Comunidad de Madrid), while other basidiomata were found growing in association either with C. ladanifer and Cistus monspeliensis in Spain or with Cistus creticus in Paros Island (Cyclades, Greece). Inocybe plesiocista forms small-sized basidiomata, characterized by fibrillose to subsquamulose pilei, smooth and narrowly ellipsoid to narrowly subamygdaliform basidiospores, slender hymenial cystidia, and few caulocystidia restricted to the apex of the stipe. In addition, phylogenetic analysis of internal transcribed spacer (ITS) and partial nuclear 28S rDNA (28S) sequences demonstrated that I. plesiocista corresponds to a distinct and strongly supported clade representing an undescribed species, related to I. ianthinopes albeit with low ITS sequence identity (86.6–87.3%) indicative of substantial genetic divergence.